Enacting Hot Potatoes to engage and motivate the undergraduate learners in the Business Correspondence course - Indrian, Ruth Dewi (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2022)
Technology has become the answer to students’ interests to be engaged in the learning process. In this case, the use of the Hot Potatoes application was employed to facilitate students’ needs in learning the Business Correspondence course. This study was a content analysis that employed the CALL approach as the assistance of students’ learning process (Egbert & Shahrokni, 2018). This study aimed to investigate the implementation of the Hot Potatoes application to assist students to learn the materials of three topics of Business Correspondence, namely Replying to a Job Applicant, Requesting a Service, and Confirming a Service (Lougheed, 2003). The results showed that the use of Hot Potatoes web-based learning brought beneficial impacts to students’ learning process of Business Correspondence course of the fourth-semester students. The researcher discovered that the implementation of this application engaged students’ attention and motivated them to be involved mindful for the learning activity. Moreover, Hot Potatoes exercises helped the students comprehend the elements of a letter and vocabulary and expressions used based on the context of the letter. The researcher suggests that future researchers can fill in the gap on how the Hot Potatoes application can be applied in various courses in English Language Departments.